Pemeriksaan Fisik dan Angka Kuman pada Ruang Tunggu Balai Pemeriksaan dan Pengawasan Penyakit Paru (BP4) Kota Ambon - M Fadly Kaliky; Rahma Tunny (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
According to the World Health Organization (WHO), 2016, there were 3.8 million people died due to poor indoor air quality. The highest number of deaths occurred in the Southeast Asia region at 1.5 million deaths while the Western Pacific region was 1.2 million, Africa 739,000, the Eastern Mediterranean 212,000, America 82,000, and Europe 52,000 deaths. Passo Health Center is directly adjacent to residential areas which results in exposure to air pollution from the surrounding environment entering the health center, causing flying bacteria or germs to enter the health center so that they can multiply in the air. This type of research is descriptive which describes the study of microbiological quality in the waiting room at the Passo Health Center. Measurement of the number of germs in the waiting room did not meet the requirements and temperature measurements, lighting in the waiting room met the requirements and humidity measurements in the waiting room did not meet the requirements based on the standards of Permemkes No. 2 of 2023 concerning Environmental Health. The number of germs and humidity in the Passo Health Center waiting room does not meet the requirements, The temperature and lighting in the Passo Health Center waiting room meet the requirements, The humidity in the Passo Health Center waiting room does not meet the requirements, The Health Center can use this research as a reference in controlling air quality both from microorganism factors and physical environmental factors.